2011
DOI: 10.1002/dev.20614
|View full text |Cite
|
Sign up to set email alerts
|

Atypical development of resting respiratory sinus arrhythmia in children at high risk for depression

Abstract: Compromised respiratory sinus arrhythmia (RSA, i.e., low cardiac vagal control) frequently characterizes clinically depressed adults and also has been detected in infants of depressed mothers; however, its existence has not been established in older at-risk offspring. We investigated developmental patterns of RSA in a sample of 163 5-14 year-old children, who were either at high risk for depression (due to having a parent with a childhood-onset mood disorder) or low-risk for depression. We hypothesized that hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 229 publications
(213 reference statements)
2
52
1
Order By: Relevance
“…ers of depression and depressive symptoms (Cowen & Wood, 1991;Gentzler, Rottenberg, Kovacs, George, & Morey, 2012;Rottenberg, Clift, Bolden, & Salomon, 2007;Schmidt, Shelton, & Duman, 2011;Yaroslavsky, Rottenberg, & Kovacs, 2013). Among potential biological markers, there has been a strong interest in respiratory sinus arrhythmia (RSA, known alternatively as cardiac vagal control, vagal tone, or high-frequency heart-rate variability; Rottenberg et al, 2007), which is a measure of parasympathetic influence on cardiac activity via the vagus nerve.…”
Section: Risk For Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…ers of depression and depressive symptoms (Cowen & Wood, 1991;Gentzler, Rottenberg, Kovacs, George, & Morey, 2012;Rottenberg, Clift, Bolden, & Salomon, 2007;Schmidt, Shelton, & Duman, 2011;Yaroslavsky, Rottenberg, & Kovacs, 2013). Among potential biological markers, there has been a strong interest in respiratory sinus arrhythmia (RSA, known alternatively as cardiac vagal control, vagal tone, or high-frequency heart-rate variability; Rottenberg et al, 2007), which is a measure of parasympathetic influence on cardiac activity via the vagus nerve.…”
Section: Risk For Depressionmentioning
confidence: 99%
“…In some studies, low resting RSA is associated with higher depression or more depressive symptoms, as would be expected. In one such study, Gentzler et al (2012) followed children between the ages of 5-14 at high risk for MDD, defined as having a parent with a childhood-onset mood disorder. The high-risk group did not show the same developmental increase in resting RSA as the low risk group.…”
Section: Rsa As a Biological Marker Of Depressionmentioning
confidence: 99%
“…For example, vagal tone and vagal reactivity can be modified by early life stress (see Field & Diego, 2008; Porges, 2011)—changes which mediate the effects of early adverse experiences on outcomes like depression (e.g., Cyranowski et al, 2011; Gentzler et al, 2012; Thayer & Brosschot, 2005). A number of studies have similarly found long-term changes in insula activity and morphology following early stress, trauma, and abuse (e.g., Ansell et al, 2012; Mueller et al, 2010).…”
Section: Individual Gender and Cultural Differences In Interoceptionmentioning
confidence: 99%
“…Descriptive analyses were conducted in SPSS 19 software (SPSS, Inc., 2011); latent variable and logistic regression models were fit in Mplus version 7.0 software (Muthén & Muthén, 2008-2012. Robust full information maximum likelihood (MLR) was used to estimate parameters adjusted for randomly missing values of dependent variables, which comprised on average 0% to 11% of the sample.…”
Section: Physiological Data Acquisition and Reductionmentioning
confidence: 99%